Effect of Aging Heat Treatment in an Al-4008 Produced by Liquid Metal Printing - Catarina Ladeiro; Francisca Nunes; Mariana Trindade; Jose Costa (U.Porto Journal of Engineering, 2024)
In today's world, additive manufacturing (AM) is one of the most popular technologies and has the potential to revolutionize the manufacturing industry. As one of the most recent advances in this industry, liquid metal printing has a growing value in the engineering field. This study aims to evaluate the effect of two heat treatment conditions in an Al-4008 alloy produced by this technique in the microstructure and mechanical properties. It was concluded that the heat treatment (HT) enhances the Si particle coalescence and Fe-rich intermetallic compound precipitation, increasing the sample hardness significantly (50%). Density analysis showed a slight porosity decrease with HT. Tensile tests indicated heat-treated, same-directionally pulled samples exhibited brittleness compared to as-printed ones, while HT increased both yield strength (245 MPa) and ultimate tensile strength (294 MPa).